Karabalgasun, Mongolei. Die Ausgrabungen im Bereich der Zitadelle der alten uighurischen Hauptstadt. Die Arbeiten der Jahre 2015 bis 2017 - Franken, Chrstina; Rohland, Hendrik; Erdenebat, Ulambayar; Batbayar, Tumurochir (e-Forschungsberichte des DAI, 2018)
Since 2013, the Mongolian-German Orchon-Expedition has been conducting research on the architectural structures of the citadel of the old Uighur capital Karabalgasun (8th/9th c. AD), located in the Mongolian Orchon valley. Over the years, large parts of the building could be recorded. The artificially constructed podium, 10 m in height, was accessible through two gateways that lead into a large, paved courtyard surrounded by smaller buildings and a major, tower-like building whose remains were found in the southeastern corner. A well, more than 10 m in depth, had been preserved in the center of the courtyard. Artifacts like fragments of jade books, processed granite capitals, gilded metal objects and a bronze bell testify to the importance of the citadel as the seat of power of the former Uighur capital.